Exploring the Relationship between Corporate Sustainability Reporting and Green Finance Investment - Moonmoon, Shahnaz Parvin; Ali, Md. Mokshud (International Journal of Business and Economics, 2026)
This study explores the relationship between corporate sustainability reporting and green finance investment, highlighting the significance of transparency in promoting sustainable investments. This research seeks to elucidate the impact of corporations' environmental, social, and governance (ESG) disclosures on the allocation of green financing investments across diverse sectors. It outlines essential facilitators, including digital tools and technology, that improve transparency in sustainability reporting and support the efficacy of green finance mechanisms. This study examines the influence of company sustainability practices on the appeal of green investments in response to the increasing global demand for sustainable financing. The research adopts a qualitative methodology, leveraging secondary data to investigate the intricate relationship between sustainability reporting and green finance. The findings indicate that comprehensive sustainability reporting is a crucial catalyst for green investments, as companies offering extensive ESG disclosures draw greater capital. The implementation of digital tools, including blockchain and artificial intelligence, enhances the transparency and trustworthiness of ESG data, hence cultivating investor trust and encouraging green investments. Nonetheless, obstacles such as varied reporting requirements and geographical inequities persist as impediments to the complete realisation of green finance's promise. The study offers both theoretical and practical contributions. It enhances the literature on green finance by underscoring the significance of transparency in corporate sustainability initiatives. It provides actionable information for governments, financial institutions, and enterprises on enhancing sustainability reporting and utilising digital platforms to attract green investments. Notwithstanding the constraints of the study, including dependence on secondary data and a sector-specific emphasis, it facilitates future enquiries into the enduring effects of sustainability reporting and the efficacy of nascent technologies in green financing. The study advocates for more examination of the efficacy of global compared to regional sustainability reporting requirements and posits that addressing legislative fragmentation is crucial for maximising the potential of green finance investments. This study establishes a foundation for subsequent research aimed at enhancing sustainable practices and digital solutions within the green finance sector.